PENGARUH KONDISI KEUANGAN PERUSAHAAN, AUDITTENURE, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP OPINI AUDIT GOING CONCERN - Alya Nur Amalina, - (2020)
This research is using quantitative study aimed to examine the effect of financial condition of the company is measured by Altman Revised method, audit tenure measured by the length of engagement between the client and public accounting firm, and reputation of public accounting firm is measured from the big four public accounting firm and non big four public accounting firm on going concern audit opinion. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013-2018. The sample in this study amounted to 91 manufacturing companies found on the Indonesia Stock Exchange and the website of each company for the period 2013-2018 which were selected using the purposive sampling method. Hypothesis testing in this study was used Logistik Regression Analysis using SPSS analysis tool with a significant level of 5%. The result of hypothesis testing showed that (1) financial condition of the company had no significant effect on going concern audit opinion (2) audit tenure had no significant effect on going concern audit opinion (3) reputation of public accounting firm had negative significant effect on going concern audit opinion.